Pengaruh Kualitas Proiduk, Citra Merek, Dan HargaTerhadap Keputusan Pembelian Produk Imitasi(Studi Kasus Pada Konsumen Sepatu Vans Di Fakultas Ekonomi Dan Bisnis Unisma) - Rasidi Rasidi; Muhammad Mansur; Khalikussabir Khalikussabir (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This research was conducted on students of the Islamic University of Malang, Faculty of Economics and Business, Department of Management, Jl. Major General Haryono 193, Dinoyo, Kec. Lowokwaru, Malang City, East Java. The purpose of the study was to determine whether product quality, brand image and price had an effect on purchasing decisions. The type of research used is quantitative research with the method of distributing questionnaires. The sample in this study was 90 respondents and data processing using SPSS computer program. The variable used in this research is Purchase Decision (dependent variable), while the independent variables are Product Quality, Brand Image and Price. This study has met the requirements of validity and reliability. Analysis of the data used in this study is the classical assumption test, multiple linear regression, hypothesis testing and analysis of the coefficient of determination. The results of this study conclude that the variables of Product Quality, Brand Image and Price have a significant positive effect on Purchase Decisions, for Vans shoes, they should be able to consider price adjustments to the needs of society in current conditions. Keywords: Product Quality, Brand Image, Price, Purchase Decision